Perlakuan Akuntansi Pajak Pertambahan Nilai dan Pengaruhnya pada Laporan Keuangan PT. Patra Darma Wijaya BalikpapanTahun 2022 - Aynaya Saffa Qathrunnada; Yudea Yudea; Dika Karlinda Sari (Al-Manar Journal of Accountancy and Business Studies, 2024)
This study aims to determine the accounting treatment of Value Added Tax by PT. Patra Darma Wijaya Balikpapan in its financial statements as a Taxable Entrepreneur (PKP). The data used are existing sources, both internal and external data, and data can be accessed via the internet and information publications. The primary data used in this study are the results of direct observations and interviews with PT. Patra Darma Wijaya Balikpapan. Secondary data used in this study were obtained from company documentation data, a brief history, and organizational structure owned by PT. Patra Darma Wijaya Balikpapan. The data collection method used in this study uses observation, interview, and documentation techniques. The results of this analysis indicate that the accounting treatment of Value Added Tax (VAT) at PT. Patra Darma Wijaya Balikpapan is in accordance with Article 28 paragraph 7 of the General Provisions of Taxation Law and the actual DPP (Law Number 7 of 2021).